(untitled) (Medico Legal Update, 2021)
The prevalence of nutritional anemia is one of elementary shool-aged children’s nutritional problems and brings an impact on students’ learning achievements. This study aimed to analyze the role of sharing peer group intervention on nutritional anemia prevention to elementary school-aged children. The research design used was quasi-experiment with control group design. Population and samples of students from IV and V classes were 54 and the students were chosen through purposive sampling method. Data were analyzed with paired test. Results showed that there were increment scores in cognitive aspect after sharing peer group method was applied as research intervention (M=24.07; SD=11.851). The value was greater than cognitive scores increment after counseling method applied as research intervention (M=14.81; SD=8.931) with p value=0.002 less than significance value (p<0,05). It shows that there is increase of average increment to respondent’s cognitive scores. Average increment affective scores of respondents after sharing peer group (M=25.55; SD=15.275) was conducted is greater than counseling method (M=15.92; SD=14.212) with p value=0.020 less than significance value (p<0.05). It means that there is increase of average increment to respondent’s affective scores. Average increment psychomotor scores of respondents after sharing peer group (M=22.22; SD=11.208) was conducted is greater than counseling method (M=15.18; SD=11.559) with p value=0.027 less than significance value (p<0.05). It means that there is increase of average increment to respondent’s psychomotor scores. It is expected to shool practitioners to continue the counseling and sharing peer group to students in order to maintain healthy food consumption pattern with sustainable and proper way so that students can avoid nutritional anemia cases.